Development of an Experimental Setup for Remote Testing Pneumatic Control - ReljiÄ‡, Vule; Bajci, Brajan; MilenkoviÄ‡, Ivana; Šulc, Jovan; Šešlija, Dragan; DudiÄ‡, Slobodan (International Journal of Online and Biomedical Engineering (iJOE), 2018)
This paper presents an experimental setup called pneumatic circular manipulator. The manipulator represents a modular setup that can be adapted to the new situation by simple transformations. It is used for testing various types of pneumatic control and energy efficiency of pneumatic control systems. The manipulator is primarily intended for students and their lectures. Since it has the possibility for remote control over the Internet, due to its modularity, it can be very interesting for researchers and employees in industry. The existing version of the manipulator allows visual monitoring of the working cycle and familiarization with the basics of pneumatic control and motion control for users. By future upgrade, the manipulator will become a setup that will provide feedback on the consumption of compressed air, analysis of the type of control, cost-effectiveness analysis etc.